Intrapartum epidural analgesia and breastfeeding: a prospective cohort study - Simpson Judy M; Roberts Christine L; Torvaldsen Siranda; Thompson Jane F; Ellwood David A (BMC, 2006)
Abstract Background Anecdotal reports suggest that the addition of fentanyl (an opioid) to epidural analgesia for women during childbirth results in difficulty establishing breastfeeding. The aim of this paper is to determine any association between epidural analgesia and 1) breastfeeding in the first week postpartum and 2) breastfeeding cessation during the first 24 weeks postpartum. Methods A prospective cohort study of 1280 women aged ≥ 16 years, who gave birth to a single live infant in the Australian Capital Territory in 1997 was conducted. Women completed questionnaires at weeks 1, 8, 16 and 24 postpartum. Breastfeeding information was collected in each of the four surveys and women were categorised as either fully breastfeeding, partially breastfeeding or not breastfeeding at all. Women who had stopped breastfeeding since the previous survey were asked when they stopped. Results In the first week postpartum, 93% of women were either fully or partially breastfeeding their baby and 60% were continuing to breastfeed at 24 weeks. Intrapartum analgesia and type of birth were associated with partial breastfeeding and breastfeeding difficulties in the first postpartum week (p < 0.0001). Analgesia, maternal age and education were associated with breastfeeding cessation in the first 24 weeks (p < 0.0001), with women who had epidurals being more likely to stop breastfeeding than women who used non-pharmacological methods of pain relief (adjusted hazard ratio 2.02, 95% CI 1.53, 2.67). Conclusion Women in this cohort who had epidurals were less likely to fully breastfeed their infant in the few days after birth and more likely to stop breastfeeding in the first 24 weeks. Although this relationship may not be causal, it is important that women at higher risk of breastfeeding cessation are provided with adequate breastfeeding assistance and support.